MANAGEMENT OF MAMMALIAN BITES AND VENOMOUS STINGS IN PRIMARY CARE - Arsić, Dragutin (PONS - medicinski časopis, 2014)
Primary care physicians should be familiar with procedure of diagnosis, treatment and triage of patients as well as prevention of transmissible diseases in animal bites and poisonous stings. The most frequent wounds from mammalian bites are of dogs, then cats, humans and rodents rarely and sporadically other domestic and wild animals. Treatment should start with primary wound care. Most wound bites have a small infection risk and routine prophylactic antibiotic is not recommended. Antibiotics useful in wound infections are amoxicillin plus clavulanic acid, ciprofloxacin, doxycycline, clindamycin, metronidazole and trimethoprim plus sulfamethoxazole. In our country, long-nosed viper and common European adder are only important species of poisonous snakes. In addition to local symptoms and hemorrhagic shock, induced by coagulopathy, other syndromes of systemic intoxication after snakebite are: neurotoxicity, myotoxicity, nephrotoxicity and early cardiovascular collapse. First aid consists of the rest and broad, compressive immobilization of affected limb. Routine use of snake antivenom is not recommended and it is given primarily during an intoxication or severe, progressive local damage. Insect bites cause allergic reactions, envenomation or transmissible infectious diseases. Local reactions in hymenoptera stings are limited and occur in non-allergic people. Mass sting events occur only in cases of numerous insect bites, usually hundreds to thousands of honey bee, tens and hundreds of wasps but a few of hornets. Treatment of severe local reaction involves limb elevation, prescription of anti-allergic drugs and anaphylactic shock care. General practitioner, according to current health regulations, must consider tetanus and rabies prophylaxis and apply them, if necessary.   Key words: bites and stings; mammals; snakes; insects; post-exposure prophylaxis.